The signal of climate changes over the last two millennia in the Gulf of St. Lawrence, eastern Canada - Wu, Xiner; De Vernal, Anne; Fréchette, Bianca; Moros, Matthias; Perner, Kerstin (Quaternary Research, 2022)
Abstract Climate changes over the past two millennia in the central part of the Gulf of St. Lawrence are documented in this paper with the aim of determining and understanding the natural climate variability and the impact of anthropogenic forcing at a regional scale. The palynological content (dinocysts, pollen, and spores) of the composite marine sediment core MSM46-03 collected in the Laurentian Channel was used to reconstruct oceanographic and climatic changes with a multidecadal temporal resolution. Sea-surface conditions, including summer salinity and temperature, sea-ice cover, and primary productivity, were reconstructed from dinocyst assemblages. Results revealed a remarkable cooling trend of about 4°C after 1230 cal yr BP (720 CE) and a culmination with a cold pulse dated to 170–40 cal yr BP (1780–1910 CE), which likely corresponds to the regional signal of the Little Ice Age. This cold interval was followed by a rapid warming of about 3°C. In the pollen assemblages, the decrease of Pinus abundance over the past 1700 yr suggests changes in wind regimes, likely resulting from increased southerly incursions of cold and dry Arctic air masses into southeastern Canada.

Insolation vs. meltwater control of productivity and sea surface conditions off SW Greenland during the Holocene - Allan, Estelle; De Vernal, Anne; Seidenkrantz, Marit‐Solveig; Briner, Jason P.; Hillaire‐Marcel, Claude; Pearce, Christof; Meire, Lorenz; Røy, Hans; Mathiasen, Anders Møller; Nielsen, Mikkel Thy; Plesner, Jane Lund; Perner, Kerstin (Boreas, 2021)
We address here the specific timing and amplitude of sea‐surface conditions and productivity changes off SW Greenland, northern Labrador Sea, in response to the high deglacial meltwater rates, the Early Holocene maximum insolation and Neoglacial cooling. Dinocyst assemblages from sediment cores collected off Nuuk were used to set up quantitative records of sea ice cover, seasonal sea‐surface temperature (SST), salinity (SSS), and primary productivity, with a centennial to millennial scale resolution. Until ~10 ka BP, ice‐proximal conditions are suggested by the quasi‐exclusive dominance of heterotrophic taxa and low dinocyst concentrations. At about 10 ka BP, an increase in species diversity and abundance of phototrophic taxa marks the onset of interglacial conditions at a regional scale, with summer SST reaching up to 10 °C between 8 and 5 ka BP, thus in phase with the Holocene Thermal Maximum as recorded in the southern Greenlandic areas/northern Labrador Sea. During this interval, low SSS but high productivity prevailed in response to high meltwater discharge and nutrient inputs from the Greenland Ice Sheet. After ~5 ka BP, a decrease in phototrophic taxa marks a two‐step cooling of surface waters. The first started at ~5 ka BP, and the second at ~3 ka BP, with a shift toward colder conditions and higher SSS suggesting reduced meltwater discharge during the Neoglacial. This second step coincides with the disappearance of the Saqqaq culture. The gap in human occupation in west Greenland, between the Dorset and the Norse settlements from 2000 to 1000 years BP, might be linked to high amplitude and high frequency variability of ocean and climate conditions.